Impact of COVID-19 Pandemic on Food Intake, Dietary Behavior, Mental Health, and Academic Performance of a Ghanaian University Students - Clement Kubreziga Kubuga; Mary Amoako; Frank Kibikal W. Nyimagnun (Hindawi Limited, 2023)
Students are one vulnerable subgroup that experience a variety of persistent pressures, high levels of stress, and poor mental health due to academic demands. COVID-19 abruptly moved education away from the classroom and mandated that instruction take place either in a small classroom setting or remotely on digital platforms, it added to the already stressed climate. Though it is established that pandemics pose stress and stress affects food intake and academic performance, little has been explored in relation to COVID-19 pandemic induced stress, diet alteration, mental health, and dietary behaviors among university students in Ghana. This study aimed to investigate the impact of COVID-19 pandemic on diet alteration, dietary behavior, mental health, and academic performance among the students of the University for Development Studies. In this cross-sectional study design (n = 94), an online survey was conducted among undergraduate students of the University for Development Studies. Data were analyzed using descriptive statistics and logistic regression models. According to the study's findings, all participants had different levels of stress, poor mental health, and problematic eating behaviors. About six out of every 10 students experienced stress induced by COVID-19 pandemic. Nearly half of the students altered their diets due to the COVID-19 pandemic. Majority of the students were also engaged in problematic eating behaviors. Additionally, academic performance of students was heavily influenced: Students who reported worse academic performance were about eight times more likely to be stressed due to COVID-19 pandemic compared to students who reported no change to their academic performance. Our findings suggest that students of UDS experience variety of pressures which were compounded by COVID-19. There is a need for programs that improve stress levels, mental health, and food intake in the university setting.